Synthesis and application of coumarin fluorescence probes - Sun, Xiao-ya; Liu, Teng; Sun, Jie; Wang, Xiao-jing (RSC advances, 2020)
In recent years, the research on fluorescent probes has developed rapidly. Coumarin fluorescent probes have also been one of the hot topics in recent years. For the synthesis and application of coumarin fluorescent probes, great progress has been made. Coumarin fluorescent probes have become more and more widely used in biochemistry, environmental protection, and disease prevention, and have broad prospects. This review introduces the three main light emitting mechanisms (PET, ICT, FRET) of fluorescent probes, and enumerates some probes based on this light emitting mechanism. In terms of the synthesis of coumarin fluorescent probes, the existing substituents on the core of coumarin compounds were modified. Based on the positions of the modified substituents, some of the fluorescent probes reported in the past ten years are listed. Most of the fluorescent probes are formed by modifying the 3 and 7 position substituents on the mother nucleus, and the 4 and 8 position substituents are relatively less modified. In terms of probe applications, the detection and application of coumarin fluorescent probes for Cu 2+ , Hg 2+ , Mg 2+ , Zn 2+ , pH, environmental polarity, and active oxygen and sulfide in the past ten years are mainly introduced. In recent years, the research on fluorescent probes has developed rapidly.